Flypaper Effect Analysis Based on Fiscal Independence Index Mapping of 2014-2023 Period - Nuriyah, Aulia Shinta; Fazaalloh, Al Muizzuddin (Journal of Development Economic and Social Studies, 2025)
The urgency of this research relates to one of the issues raised in the RPJMN 2020–2024 regarding decentralization and regional independent, namely the high dependence of local govenrments on transfer funds and the fiscal independence disparity among regions, as highlighted in the review report by the BPK RI. The objective of this study is to analyze the presence or absence of the flypaper effect based on the mapping of the fiscal independence index in provincial governments categorized as not yet independent, towards independence, and independent. Using purposive sampling, the study selected 33 provinces during the 2014–2023 period. The research utilized secondary data from DJPK Ministry of Finance, and applied a panel data multiple linear regression method. The result that flypaper effect occurs in provinces classified as not yet independent, whereas it does not occur in provinces categorized as towards independence and independent. This research provides empirical evidence that the flypaper effect does not occur uniformly across Indonesia. Moreover, this study contributes to filling the research gap by applying a new approach in analyzing the flypaper effect through the classification of provinces based on fiscal independence index mapping.